A Practical ITO Replacement Strategy: Sputtering‐Free Processing of a Metallic Nanonetwork. Issue 8 (30th May 2017) - Xian, Zhike; Han, Bing; Li, Songru; Yang, Chaobin; Wu, Sujuan; Lu, Xubing; Gao, Xingsen; Zeng, Min; Wang, Qianming; Bai, Pengfei; Naughton, Michael J.; Zhou, Guofu; et al.
Abstract : Metallic network, an important indium tin oxide (ITO) replacement, is extensively studied due to its advantages in optoelectronic properties and mechanical flexibility. Vacuum sputtering/evaporation‐free processing is an essential step for roll‐to‐roll production of low‐cost and large‐size metallic network transparent electrodes. In this paper, a high performance metallic crack‐nanonetwork (CNN) is demonstrated by employing a sputtering/evaporation‐free process, which combines advantages of the standard CNN processing with electroless plating, enabled by unique properties of the commercial amorphous fluoropolymer CYTOP. This network shows outstanding optoelectronic performance, with the best figure of merit ≈ 20000 (at T ≈ 86.4% and R s ≈ 0.13 Ω sq −1 ), as well as excellent mechanical flexibility and stability. This network outperforms the current industry standard, ITO, in performance and cost, as a result of the elimination of the sputtering/evaporation step. This is therefore a dramatic step toward replacing ITO with a metallic cracking nanonetwork. Abstract : A high performance metallic crack‐nanonetwork is demonstrated by employing a sputtering/evaporation‐free, solution based process. This network shows outstanding optoelectronic performance, with the figure of merit ≈ 20000 (at T ≈ 86.4% and R s ≈ 0.13 Ω sq −1 ), as well as excellent mechanical flexibility and stability. This network outperforms the current industry standard, indium tin oxide (ITO), it is therefore a viable, practical ITO replacement.